FACTORS RELATED TO OCCUPATIONAL SAFETY AND HEALTH SYSTEMS AMONG COAL HANDLING WORKERS AT MEULABOH SEAPORT - Dedek Kasmiyanda; Marniati; T. Alamsyah; Firman Firdaus Saputra; Zakiyuddin (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2025)
Coal loading and unloading workers at Meulaboh Seaport are at high risk of accidents and health problems due to dust exposure, heavy workloads, and unsafe working conditions. Although the Occupational Safety and Health (OSH) management program has been implemented, its execution remains low. Many workers are not disciplined in using Personal Protective Equipment (PPE), OSH training is not optimal, and supervision is still weak. This study aims to analyze the factors associated with the implementation of OSH management programs among loading and unloading workers at Meulaboh Seaport. The study used a quantitative method with a cross-sectional design and involved 32 respondents. Data analysis was conducted using univariate and bivariate techniques. The results showed a significant relationship between work discipline (p = 0.005), training (p = 0.010), supervision (p = 0.022), and OSH evaluation (p = 0.010) with the implementation of the OSH management program. It is recommended that the management of Meulaboh Seaport, as the company’s policy maker, continuously improve the existing OSH management system to ultimately enhance worker performance, which will bring both financial and non-financial benefits to the seaport. For workers, it is advised to prioritize occupational safety and health by complying with the established OSH management system.